2021
DOI: 10.21595/jve.2021.22029
|View full text |Cite
|
Sign up to set email alerts
|

Seismic performance analysis of self-centering segment piers with mortise-tenon shear connectors based on cyclic pseudo-static test

Abstract: In the past decades, more and more precast piers have been used in actual engineering, which brings convenience in construction and standardization of production. However, precast piers still have some shortcomings, such as shear slip between segments and poor energy dissipation. Thus, a self-centering mortise-tenon segmental bridge pier was proposed in this paper. To research the seismic performance of the self-centering mortise-tenon segment piers, three scaled model piers with their scale ratio as 1:3 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The research results showed that the ductility of piers with steel sleeves or stirrups was significantly improved, while the concrete protective layer was obviously cracked. In 2006, was proposed by Yongjun Ni [36].…”
Section: Introductionmentioning
confidence: 99%
“…The research results showed that the ductility of piers with steel sleeves or stirrups was significantly improved, while the concrete protective layer was obviously cracked. In 2006, was proposed by Yongjun Ni [36].…”
Section: Introductionmentioning
confidence: 99%